Universities' role on tobacco control law support in Thailand - Pongsri Srimoragot (Tobacco Induced Diseases, 2018)
Background and challenges to implementation In Thailand, Tobacco control laws had announced since 2535 B.E. So that tobacco product, marketing, and sponsorship and consuming of tobacco is advanced and not effective to control. As seen from the prevalence of tobacco smoking did not reduce and its trend to increase especially among youth and women. So Ministry of public health in Thailand was begin to renovate, improve, and readjust both tobacco control law. On the process of law revision, the main objective was set to protect all adolescent from starting to be the new comer and to be consistent with WHO FCTC.